Reflexive management in formation of financial results of cooperation of power and enterprise structures - D. T. Novikov; B. G. Khairov (Вестник СибАДИ)
The article dwells upon the questions of managing organization in modern conditions. There are determined features of the timber industry in the conditions of globalization. Transformation of relations between its subjects requires the search for new models of market financial coordination. On the basis of considered, by the authors, problem, it is determined that the standard models of management do not allow to adapt the business to prevailing conditions in the Russian forest complex. The authors give recommendations for the use of reflexive control to form relations with counterparties in the form of multilateral partnership.